Asymptotic Expansion for Distribution Laws of the Arithmetic Multiplicative Functions - Manstavičius, E. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Манставичюс. Асимптотическое разложение законов распределения мультипликативных арифметических функцийE. Manstavičius. Aritmetinių multiplikatyvinių funkcijų pasiskirstymo dėsnių asimptotinis išdėstymas